Comparison of The Effectiveness Between Fentanyl and Ketamine as Adjuvant Epidural Analgesia with Ropivacaine In Post Operation of The Lower Extremity - Pratama, Mhd. Rizki; Ihsan, Mhd.; Hamdi, Tasrif; Eyanoer, Putri Chairani (JAI (Jurnal Anestesiologi Indonesia), 2025)
Background: One typical side effect that frequently follows surgery is pain. Lower limb surgery procedures can cause tissue and nerve damage. When compared to systemic opioids, epidural analgesia provides better postoperative analgesia. Adjuvants extend and intensify sensory blockage, which increases the effectiveness of local anesthesia. They also cause the dose of local anesthetic drugs to be reduced.Objective: To determine the comparative effectiveness of adjuvant fentanyl compared with ketamine and ropivacaine as adjuvant epidural analgesia in post-lower extremity surgery patients.Methods: The purpose of this randomized controlled experiment is to compare the efficacy of ketamine and fentanyl as adjuvant epidural analgesia in postoperative lower extremities when combined with ropivacaine. In this study, two groups of patients were given epidural anesthesia: the first group received ropivacaine 0.25% with 125 mcg of fentanyl adjuvant, while the second group received ropivacaine with 0.25% with ketamine 10 mg. The double-blind technique was used to select a total sample of 29 individuals from each group based on inclusion and exclusion criteria. The assessment of pain scores, hemodynamics, treatment-related side effects, and bromage scores was used to test both groups.Result: The T5 assessment showed a substantial difference in the pain scores at rest. With a total of 14 side effects, blood pressure and pulse rate fluctuations were the most common, accounting for 20% of the side effects. Despite this, patients in the ropivacaine + ketamine adjuvant group continued to experience hemodynamic stability and comfort. There were two side effects in the fentanyl combination group, with nausea being the most common. Between the therapy groups, there was no difference in the recovery of the bromage score (p>0.05).Conclusion: Ropivacaine-ketamine has favorable effectiveness as an analgesia adjuvant compared to ropivacaine-fentanyl.